Biological Management of Basal Rot of Onion by Trichoderma harzianum and Withania somnifera - AKHTAR,R. (2018)
ABSTRACT: Onion is attacked by destructive soil-borne fungal plant pathogen Fusarium oxysporum f. sp. cepae, resulting in basal rot disease. In the present study, three Trichoderma species (T. pseudokoningii, T. harzianum and T. reesei) and leaves of solanaceous weed Withania somnifera were used for management of this disease. The in vitro interaction study revealed T. harzianum as the most effective biocontrol agent against the pathogen. In a pot trial, dried leaf material of W. somnifera (1%, 2% and 3% w/w) and inoculum of T. harzianum were mixed in the pot soil previously inoculated with the pathogen. The highest incidence of the disease (87%) was found in positive control (pathogen inoculation without any amendment). Different rates of dry leaf material reduced the incidence of the disease to 41-66%. T. harzianum in combination with leaf material reduced the incidence of the disease to 20-53%. In a laboratory bioassay, the dry leaf extract of W. somnifera was prepared in methanol and partitioned with n-hexane, chloroform, ethyl acetate and n-butanol. The highest concentration (200 mg mL-1) of all except for the n-butanol fraction significantly decreased fungal biomass over control. This study concludes that basal rot of onion can be controlled by combined application of W. somnifera dry leaf material and biological control agent T. harzianum.